2021
DOI: 10.52198/21.sti.38.so1424
|View full text |Cite
|
Sign up to set email alerts
|

The Artisential® Articulated Laparoscopic Forceps: A Dry Lab Study to Examine Dexterity and Learning Effects in Operators with Different Levels of Laparoscopic Experience

Abstract: Purpose: The advent of robotic surgery has highlighted the advantages of articulation. This dry-lab study examined the dexterity and learning effect of a new articulated laparoscopic instrument: the ArtiSential® forceps (LIVSMED, Seongnam, Republic of Korea). Methods: A peg board task was designed. Three groups of volunteers with varying levels of laparoscopic expertise were organized to perform the task: expert, intermediate and novice. The participants performed the task using articulated and straight instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The shaft diameter is 10 mm [11,12] The ArtiSential ® (Figure 3E) is an 8 mm diameter pistol-handle instrument. It has zero ben radius when deflected; its wrist function is guaranteed by two joints at the end effector that couples their movements with the ones of the handle [13][14][15][16][17][18].…”
Section: Intuitool ® (Unemed Corporation Omaha Ne Usa)mentioning
confidence: 99%
“…The shaft diameter is 10 mm [11,12] The ArtiSential ® (Figure 3E) is an 8 mm diameter pistol-handle instrument. It has zero ben radius when deflected; its wrist function is guaranteed by two joints at the end effector that couples their movements with the ones of the handle [13][14][15][16][17][18].…”
Section: Intuitool ® (Unemed Corporation Omaha Ne Usa)mentioning
confidence: 99%
“…After acquiring ARTISENTIAL ® early in 2020, our surgical department initiated a dry lab training for its medical staff. Soon afterwards, our group conducted a study which confirmed at least a good understanding and command of the ARTISENTIAL ® instruments by our surgeons [21]. Since then, more than 40 surgical procedures, including colorectal resections for benign and oncologic indications, mesh rectopexies and hernia repair, were performed with ARTISENTIAL ® at our institute.…”
Section: Introductionmentioning
confidence: 75%
“…2). This basically eliminates the fulcrum effect principle, known from standard laparoscopy [21]. All procedures in this study were performed with the ARTISENTIAL ® monopolar spatula and the ARTISENTIAL ® bipolar forceps (Fig.…”
Section: Artisential ®mentioning
confidence: 99%
See 1 more Smart Citation
“…[11]. Neben den hochkomplexen und teuren RAS-Masterand-Slave-Systemen haben sich jüngst mehrere Anbieter von Laparoskopiesystemen mit roboterähnlichen Eigenschaften vornehmlich im Hinblick auf Triangulationsmöglichkeiten platziert [12][13][14].…”
Section: In Diesem Beitragunclassified